Features of Case Follow-up of Extremely Preterm Infants - О.S. Yablon; D.Yu. Vlasenko; D.P. Sergeta; К.T. Bertsun; О.V. Kharchuk; N.А. Shovkoplyas; Т.А. Vlasenko (Zaslavsky O.Yu., 2014)
Objective. The study was conducted to analyze and improve the quality of case follow-up of children with birth weight < 1000 g and gestational age ≤ 28 weeks. Materials and Methods. The study group comprised 42 children, for whom case follow-up was conducted, which included control of disease rate, sensory functions, psychomotor and social-emotional development, comorbid conditions until at least 18 months of corrected age. The comparison group included 36 children with a standard observation. Results. The study showed a reduction in the incidence of postneonatal mortality by half, as well as decrease in the prevalence of cerebral palsy by 7.5 %. Qualitative clinical examination enables to detect timely abnormalities in sensory, motor, cognitive and socio-emotional development, to apply the techniques of early rehabilitation and to reduce disability in extremely premature infants.